Gospodarcze interregnum w obliczu światowych przemian gospodarczych XXI wieku - Maryniak, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
According to Adam Smith’s teaching, the economic development is credited to the entrepreneurs. The source of a nation’s wealth is the right allocation of resources. This allocation can be made mainly by an entrepreneur who by aiming for meeting his or her own needs indirectly influences the development of the whole society. However, societies start to shift from their countries. The opponents of capitalism attack mainly the rapacity of entrepreneurs, and incompetence of the authorities.When referring to the best thriving economies of the last several years, their economic slowdown is emphasised. Even the strongest economies of the European Union do not cope with the return to the path of sustainable growth, and the United States struggles with the largest deficit for years and increasing unemployment.The economic development of several Asian countries can be considered as unusual. The People’s Republic of China has been the leader of this group for many years. What is distressing, though, is the fact that despite being the leading world economy and contributing considerably to the world’s economic growth, China poses a threat in the social sphere.The Chinese expansion in Africa contributes considerably to the devastation of local natural environment.In addition, the population problems of capitalist economies are not without importance. Most of the European nations are dying nations. Muslim nations are a serious threat for them. The changing model of the family negatively influences functioning of liberal societies, which indirectly contributes to the state of their economies.Indisputably, liberal values and capitalism represented by the European Union or the United States start to have a menacing opponent. Asian countries, and China especially, prove that an economic success is also possible with much less of a social base, and restriction of democracy. The world is still divided into two polar models of economic systems — on the one side represented by communist China and on the other by the liberal United States. Currently, we have no truck with interregnum in the area of world economy but with two kings.
Keywords: kapitalizm; kryzys; wolny rynek; interregnum; zależność ekonomiczna